Study the effect of gas channel surface on anode supported planar of Solid oxide fuel cell performance - Horr, Sabrina; Hocine, Mohcene (University of Eloued جامعة الوادي, 2018)
This study focuses on the effect of gas channel surface on the performance of solid oxide fuel cell using ANSYS FLUENT. Firstly the model is validated using one of the available numerical results from previous researches the comparison between the numerical model and the reported results shows very good agreement. Secondly Study the Mesh independency to ensure that the model results are independent of the grid size. Two different configurations of the Solid Oxide Fuel Cells are examined :i) the Anode Supported Planar Solid Oxide Fuel Cell (ASP_SOFC) with channel gas surface 1mm² and ii) ASP_SOFC with channel gas surface 0.25mm². This study modeled and compared the performance of a single SOFC at T=1123K under the specified inlet operating conditions.
International Symposium on Mechatronics and Renewable Energies El-Oued 10- 11 December 2018
Keywords: Solid oxide fuel cell, Performance SOFC, channel gas, ANSYS FLUENT, modeling, simulation